Cytostatics occupational exposure: genotoxic effects assessment - Ladeira, Carina (2014)
The use of cytostatics drugs in anticancer therapy is increasing. Health care workers can be occupationally exposed to these drugs classified as carcinogenic, mutagenic or teratogenic. Workers may be exposed to this drug, being in the hospital settings the main focus dwelled upon the pharmacy, and nursing personnel. Although the potential therapeutic benefits of hazardous drugs outweigh the risks of side effects for ill patients, exposed health care workers can have the same side effects with no therapeutic benefit. The exposure to these substances is epidemiologically linked to cancer and nuclear changes detected by the cytokinesis-block micronucleus test (CBMN). This method is extensively used in molecular epidemiology, since it determines several biomarkers of genotoxicity, such as micronuclei (MN), which are biomarkers of chromosomes breakage or loss, nucleoplasmic bridges (NPB), common biomarkers of chromosome rearrangement, poor repair and/or telomeres fusion, and nuclear buds (NBUD), biomarkers of elimination of amplified DNA.